ASSESSMENT OF CAESAREAN SECTION RATE USING ROBSON TEN GROUP CLASSIFICATION SYSTEM IN A TERTIARY CARE HOSPITAL: A CROSS SECTIONAL STUDY - Nazeer, Saira; Memoona Rehman,; Saba Khan,; Sadia Sadiq,; Khadija Bano, (Journal of Ayub Medical College Abbottabad, 2023)
Background: The growing rate of caesarean section is a major concern for quality of maternal life and public health. Concerns about such increases prompted the WHO to recommend Robson ten group classification system for assessing the Caesarean Section rate. The present study's aim was to assess the caesarean rate using Robson's ten group classification system and highlighted the reliable information system, in turn, helps to construct interventions to reduce avoidable caesareans. Methods: This cross-sectional study was carried out on 5796 women who delivered from 25th November 2021 to 24th November 2022 in Jinnah Post Graduate medical Centre Karachi. Data was collected from the women admitted for delivery using Robson's pro forma. Relative size and caesarean rate of each group and overall caesarean section rate was calculated. Results: Of the total 5796 deliveries, 2141 (36.9%) were caesarean deliveries and 3655 (63.1%) had normal deliveries. Out of Robson's ten groups system, Group 10 had a higher contribution of 705 (12.2%) to the overall caesarean rate followed by group 5 had 627 (10.8%). The contributing prevalence of Group 1, 2, 3, 4, 6, 7, 8 and 9 were 122 (2.1%), 317 (5.5%), 50 (0.87%), 167 (2.9%), 42 (0.72%), 35 (0.6%), 49 (0.85%) and 27 (0.46%) respectively. Conclusion: Our study concluded that Group 10 and 5 were the most responsible for the whole Caesarean Section rate. In all contributing groups, there is a need to identify the indications and to sub classify these groups further so that preventable caesarean sections can be avoided by reducing these factors.